The Importance Of Keeping Health During Pandemic - Asri Solihat; Agung Trisna Mukti; Lucky Luqmanul Hakim Ramadhan; Ryski Dwi Syahputra; Sopian Wibiksana (Indonesian Journal of Community Empowerment (IJCE), 2021)
Abstract The corona virus pandemic (COVID-19) has not only threatened physical health, but has also threatened the mental health of many people. A virus that has claimed thousands of lives around the world until now and has caused a lot of concern among the public every minute the community is always bombared with news and information about COVID-19 both through TV, social media and the internet. So do not be surprised if many people experience mental disorders such as excessive worry in the midst of a pandemic of diseases caused by the corona virus. Some mental disorders that often arise today, for example, easily carried emotions, stress, excessive anxiety, depression, and so on. Anxiety and mental disorders will then cause imbalances in the brain, which in turn arises into a psychological disorder, or also called psychosomatic. When a person experiences psychosomatic symptoms, he can feel symptoms such as COVID-19 disease, which is feeling fever, dizziness, or a sore throat, even though his body temperature is normal. Abstrak Pandemi virus corona 2019 (COVID-19) bukan hanya mengancam kesehatan fisik, tetapi juga telah mengancam kesehatan mental banyak orang. Virus yang telah menelan ribuan korban jiwa di seluruh dunia hingga sampai sekarang ini dan telah menimbulkan banyak kekhawatiran di kalangan masyarakat. Setiap menit, masyarakat selalu dihujani oleh berita dan informasi seputar COVID-19, baik melalui TV, media sosial, serta internet. Maka tak heran jika banyak masyarakat mengalami gangguan mental seperti rasa kekhawatiran yang berlebihan di tengah pandemi penyakit yang ditimbulkan oleh virus corona tersebut. Beberapa gangguan mental yang kerap timbul dewasa ini misalnya mudah terbawa emosi, stres, cemas berlebihan, depresi, dan sebagainya. Kecemasan dan gangguan mental ini kemudian akan menimbulkan ketidakseimbangan di otak, yang pada akhirnya timbul menjadi gangguan psikis, atau disebut juga psikosomatik. Ketika seseorang mengalami gejala psikosomatik, maka ia bisa merasakan gejala seperti penyakit COVID-19, yakni merasa demam, pusing, atau sakit tenggorokan, padahal suhu tubuhnya normal.